Saga - Vol 9 Volume nine - Vaughan, Brian K.; Fonografiks; Image Comics (Portland, Oregon : Image Comics, Inc., 2018)
"After the traumatic events of the War for Phang, Hazel, her parents, and their surviving companions embark on a life-changing adventure at the westernmost edge of the universe."--Provided by publisher.
"Originally published in single magazine form as Saga #49- 54"--Indicia.
Rated M: Mature.
Keywords: Families; Comic books, strips, etc; Life on other planets; Comic books, strips, etc; Imaginary wars and battles; Comic books, strips, etc; Comic books, strips, etc. -- United States; Families; Comic books, strips, etc; Cartoons and comics -- United States; Fantasy comics; Science fiction comics; Comics (Graphic works)